Kebudayaan dan Kearifan Daulah Abbasiyah: Warisan Peradaban Islam - Mauldia Aslamiyah; Nurjanah; Karmelia Putri; Azkia Savitri (Tanjak: Sejarah dan Peradaban Islam, 2024)
This journal is intended to provide a general overview of the legacy of Islamic civilization during the time of Daulah the Abbasid, who ruled from 750 to 1258 after being elected by the second Abbasid caliph in 762 with headquarters in Baghdad and then moved to Samara in the ninth century. The Abbasid dynasty lasted for about five centuries, from 132 AD or 750 AD to 1258 AD. The method used by library research, using widely available literary sources, such as books, journal articles, research reports, and other electronic documents from online libraries or databases. Data obtained from journal sources relevant to the heritage of Islamic civilization in the Abbasian era include the advancement of educational sciences, the creation of literary and artistic works, and the widespread economic development in the spread of Islam during the Abbassian era. The heritage of Islamic civilization from the Abbasid era has had a major impact on Muslim society as a whole and such heritage is evidence of wealth and intellectual and artistic wealth.